Coastal resource management initiatives of the local government of Bacolod City issues, thrusts and directions - Sardua, Raquel Roldan (University of the Philippines in the Visayas, 2002)
The study was conducted to identify the CRM initiatives implemented by the Bacolod City government with aim of providing directions for the management of coastal resources. The study also looked into the issues and concerns that affect the sustainability of these initiatives for the effective management of coastal resources in the city. The dat and information were generated through focused group discussion and interviews with stakeholders that included the city officials, coastal residents and fisherfolks who are members and officers of fisherfolk organizations. Among the initiatives that were undertaken by the city government were the creation of FARMC's enactment of local fishery ordinances, updating of fisherfolk registry in the coastal barangays, creation of Bantay Dagat Task Force which serves as the enforcement arm of the city on the implementation of fishery policies and ordinances, and the identification of fishery development zones as part of the Strategic Agriculture and Fishery Developement Zone (SAFDZ) of Bacolod City for inclusion in the city's comprehensive land use plan. Issues and concerns at the community level include the rampant illegal fishing in the city's territorial waters, weak law enforcement, and the perceived lack of support of barangay and city officials in program/project implementation. Success of CRM intiatives rests largely on strong political will and leadership of LGU officials. The City of Bacolod, to date, has no comprehensive CRM plan and there appears a poor coordination in the implementation of these initiatives. Moreover, projects and activities were undertaken in a fragmented manner. Participation and involvement of stakeholders likewise were difficult to solicit. The city government should formulate a comprehnsive CRM plan which must involve all the stakeholders in the planning process. The plan will provide the legal and financial framework to sustain the initiatives already started. Participation of all stakeholders is a prerequisite to the effective implementation of the city's CRM program.